Experimental Study Of Multi-Point Incremental Forming For Conical Parts - S. Faraj; Y. Rostamiyan; A.A. Shamsi Sarband (مهندسی مکانیک شریف, 2023)
The development of rapid prototyping methods has been very drastic in recent years. One of these methods, with a nature similar to sheet-forming processes, is the incremental forming method. In the last two decades, this technique has attracted much attention in industrial applications. The incremental forming process has been able to play a major role in advancing industrial projects in the production of low-volume prototypes. This process is a suitable alternative to conventional forming processes in the single production of conical geometries because of the low cost of machinery, equipment, and tools. In this paper, the two-point incremental forming of conical parts by three multi-point matrix designs, including single, double, and three-step cylinders, were investigated. For this purpose, the feed rate (400-1000 mm/min) and the penetration step of the tool (0.5-1.1 mm) were investigated in three levels to form the aluminum sheets with a thickness of 0.5 mm. In the following, the effect of the input parameters on the limiting height of the formed specimens, thickness distribution, surface roughness, and geometric accuracy of longitudinal cut specimens was assessed. According to the results, using the multi-point matrixes, despite increasing the final geometric accuracy, friction was reduced compared to the conical matrix. Using a two-step matrix, deeper pieces were formed by increasing the formability of the sheet, in which the average height was improved by an average of 12%. However, no significant change was observed in the roughness of the samples formed by all three types of matrixes. Therefore, the design of the proposed matrix had almost no tangible effect on the final surface roughness output. From the view of geometric accuracy, the matrix design with three steps created the highest geometric accuracy, as well as the least deviation relative to the planned path.